SHARIA FINANCIAL LITERATURE IN PROMOTING RELIGIOUS MODERATION IN INDONESIA - Bahri S, Andi; Mahmadah Hanafi, Syafiq; Markarma, Andi; Megandani, Adi (Jurnal Lektur Keagamaan, 2022)
ABSTRACT Sharia financial literacy, especially for the younger generation is one among focuses of the Financial Services Authority (OJK) programs. As the largest age group in Indonesia, young people have the potential to become the users and actors of Islamic finance. On the other hand, this age group is also vulnerable to associating 'sharia' with economic activeties which may not be in line with the national vision of religious moderation. One of the efforts made by OJK is publishing Sharia finance textbooks. This study examines the content of values and culture in the Sharia financial literacy textbook by the OJK and its relation to the national vision of religious moderation. This research employs qualitative descripttive method, where data was collected through interviews, observations and text analysis. The main data of this study were financial literacy textbooks by OJK, which were analyzed to obtain the elements of Islamic financial literacy and cultural characteristics that uphold tolerance and religious moderation. The study found that the Islamic financial literacy series contains inclusive content where the characters in the book use local Indonesian names from diverse ethnics and religious backgrounds. In addition, the Sharia financial literacy series also promotes the values of professionalism, commitment and tolerance. Thus, it can be concluded that the content of Islamic financial literacy published by OJK is in accordance with the vision of religious moderation. Keywords: Financial Services Authority (OJK), Religious Moderation, Sharia Financial Literature, Young Generation.  ABSTRAK Literasi keuangan syariah terutama terhadap generasi muda menjadi salah satu fokus program Otoritas Jasa Keuangan (OJK). Hal ini dikarenakan generasi muda yang menjadi kelompok usia terbesar di Indonesia berpotensi menjadi pengguna dan pelaku keuangan syariah. Di sisi yang lain, kelompok usia ini juga rentan mengasosiasikan ‘syariah’ dengan kegiatan perekonomian yang bisa jadi tidak sejalan dengan visi moderasi beragama. Salah satu upaya yang dilakukan OJK untuk meningkatkan tingkat literasi keuangan generasi muda adalah dengan menerbitkan buku teks keuangan syariah. Penelitian ini mengkaji muatan nilai dan budaya dalam buku literasi keuangan syariah oleh OJK dan kaitannya dengan visi nasional moderasi beragama. Penelitian ini adalah kualitatif deskriptif, dimana data dikumpulkan melalui wawancara, pengamatan, dan analisis teks. Data utama penelitian ini adalah buku teks literasi keuangan, yang kemudian dianalisis untuk mendapatkan esensi literasi keuangan syariah serta karakter budaya yang menjunjung sikap toleransi dan moderasi beragama. Hasil penelitian menunjukkan bahwa seri literasi keuangan syariah memuat konten yang inklusif dimana karakter yang ada di buku tersebut menggunakan nama-nama lokal khas Indonesia dari latar belakang etnik dan agama yang beragam. Selain itu, seri literasi keuangan syariah ini juga mempromosikan nilai profesionalisme, komitmen dan toleransi. Dengan demikian, dapat disimpulkan bahwa konten literasi keuangan syariah yang diterbitkan oleh OJK ini sesuai dengan visi moderasi beragama.  Kata kunci, Generasi Muda, Literasi Keuangan Syariah, Moderasi Beragama, Otoritas Jasa Keuangan (OJK).